Chronic Subdural Hematoma Caused by Acute Myeloblastic Leukemia: A Case Report - Xia, Guangwen; Zhang, Weitao; Xiao, Jing; Shi, Lin; Zhang, Yiming; Xue, Hang (Frontiers in Neurology, 2022)
Chronic subdural hematoma, a common neurosurgical disease, is mostly caused by craniocerebral trauma. Chronic subdural hematoma caused by acute myeloblastic leukemia is rarely reported, and its pathogenesis and strategies for clinical treatment remain controversial. Here, we report a case of chronic subdural hematoma caused by acute myeloblastic leukemia. We reported a rare case of chronic subdural hematoma caused by acute myeloblastic leukemia. The patient’s condition deteriorated quickly after admission, and emergency trepanation and drainage of the chronic subdural hematoma was performed, followed by oral treatment with atorvastatin. Platelet levels continued to decrease during neurosurgical treatment. Bone marrow cytology, flow cytology, and karyotype analysis suggested acute myelocytic leukemia (AML). Then, the patient was transferred to the hematology department for chemotherapy treatment, during which there was no hematoma recurrence. Chronic subdural hematoma caused by acute myeloblastic leukemia is a very rare disease. Surgery should be performed when the intracranial hematoma is more than 10 mm thick and the midline structures are displaced by more than 5 mm, and postoperative treatment should be supplemented with atorvastatin to prevent recurrence. Chemotherapy should be given promptly to treat leukemia after stabilization of neurological conditions.